Development of a Multidomain Conceptual Framework for Frozen Shoulder: A Systematic Review Integrating Clinical, Biological, Psychological and Lifestyle-Related Contributors - Santiago Navarro-Ledesma; José Javier Pérez-Montilla; Dina Hamed-Hamed; Fabrizio Brindisino; Filip Struyf (Journal of Clinical Medicine, 2026)
Background/Objectives: Frozen shoulder (FS) is increasingly recognised as a heterogeneous condition in which clinical presentation, metabolic/endocrine burden, imaging phenotype, psychological factors, lifestyle-related contributors, and inflammatory biology may all contribute to disease expression and outcome. However, these contributors have not previously been integrated within a unified multidomain framework for whole-person phenotyping. To develop an evidence-derived multidomain conceptual framework for FS by integrating clinical, biological, psychological, and lifestyle-related contributors into a clinically interpretable structure. Methods: A systematic review with quantitative evidence synthesis was conducted following methodological principles for systematic reviews and reported in accordance with PRISMA 2020. The protocol was registered in PROSPERO (CRD420251158406). Observational studies relevant to predefined FS domains were identified, classified according to analytic contribution, and synthesised using a structured evidence-weighted approach. Where quantitative pooling was methodologically appropriate, meta-analytic synthesis was undertaken; where heterogeneity precluded conventional pooling, evidence was integrated through structured domain-level quantitative synthesis. Within-sphere and cross-sphere weights were derived from directness, consistency, prognostic or phenotyping relevance, methodological robustness, risk-of-bias profile, and domain specificity, and should be interpreted as exploratory evidence-derived estimates. Results: The final multidomain corpus comprised 63 studies, including 39 allocated to the clinical sphere, 5 to the metabolic/endocrine sphere, 10 to the psychological sphere, 8 to the imaging sphere, and 1 to the inflammatory sphere as direct but lower-confidence support. The final exploratory framework retained five spheres: clinical, metabolic/endocrine, imaging, psychological, and inflammatory. Within-sphere weighting identified baseline stiffness/range-of-motion restriction and symptom duration as dominant clinical components, diabetes-related burden and glycaemic control as dominant metabolic/endocrine components, capsular structural biomarkers as dominant imaging components, distress/mood together with sleep-related burden as dominant psychological components, and IL-1β-related biomarker and susceptibility evidence as the principal retained inflammatory signal. Provisional cross-sphere weighting yielded global contributions of 24.0% for the metabolic/endocrine sphere, 22.9% for the imaging sphere, 21.1% for the clinical sphere, 20.0% for the psychological sphere, and 12.0% for the inflammatory sphere. Conclusions: FS appears to be more appropriately represented as a weighted multidomain condition than purely as a clinical stiffness syndrome. The identified domains should not be interpreted as isolated entities, but rather as interacting and overlapping contributors within a whole-person clinical presentation. The proposed framework should be interpreted as an initial conceptual platform for future validation and personalised treatment-allocation research rather than as a clinically validated decision-support tool.